2013
DOI: 10.3389/fnins.2013.00225
|View full text |Cite
|
Sign up to set email alerts
|

Predeliberation activity in prefrontal cortex and striatum and the prediction of subsequent value judgment

Abstract: Rational, value-based decision-making mandates selecting the option with highest subjective expected value after appropriate deliberation. We examined activity in the dorsolateral prefrontal cortex (DLPFC) and striatum of monkeys deciding between smaller, immediate rewards and larger, delayed ones. We previously found neurons that modulated their activity in this task according to the animal's choice, while it deliberated (choice neurons). Here we found neurons whose spiking activities were predictive of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 70 publications
3
27
0
1
Order By: Relevance
“…In this vein, we showed that when monkeys were deciding between smaller, more immediate rewards and larger, delayed ones, their choices could be decoded from single-neuron activity in frontal cortex and the basal ganglia before they were even informed of the delays associated with the decision alternatives, and hence before rational deliberation could begin. As expected, and as the circuit model we devised suggested, the bias activity was more predictive as the values of the two alternatives became more similar (Maoz, Kim, Rutishauser, Lee, & Koch, 2010;Maoz et al, 2013). In all the Libet experiments and follow-ups discussed above, the values associated with the random left-or right-hand movements were generally similar, if not identical.…”
Section: Follow-up Experiments That Do Not Rely On Readiness Potentialsupporting
confidence: 56%
“…In this vein, we showed that when monkeys were deciding between smaller, more immediate rewards and larger, delayed ones, their choices could be decoded from single-neuron activity in frontal cortex and the basal ganglia before they were even informed of the delays associated with the decision alternatives, and hence before rational deliberation could begin. As expected, and as the circuit model we devised suggested, the bias activity was more predictive as the values of the two alternatives became more similar (Maoz, Kim, Rutishauser, Lee, & Koch, 2010;Maoz et al, 2013). In all the Libet experiments and follow-ups discussed above, the values associated with the random left-or right-hand movements were generally similar, if not identical.…”
Section: Follow-up Experiments That Do Not Rely On Readiness Potentialsupporting
confidence: 56%
“…In addition, a later study by Maoz and colleagues demonstrated that the caudate preferentially contained “choice neurons,” a population of cells that tracks the actual choice by changing their activity accordingly (Fig. A) . Importantly, the choice‐related activity in the dorsal striatum exerted a more powerful influence on the behavioral result than the spatial bias–related activity in the ventral striatum.…”
Section: Evidence From Animal Model Studiesmentioning
confidence: 94%
“…(A) Modeling caudate activity for the reward valuation during intertemporal choice based on the biophysical association of neural activity with brain hemodynamic response . Caudate “choice neurons” encode the difference in temporally discounted values of intertemporal choice, which may manifest as the BOLD signal associated with reward valuation . In adults, the BOLD signal associated with immediate choice (immediate‐BOLD) is larger than the BOLD signal associated with delayed choice (delayed‐BOLD) as observed in Refs.…”
Section: Evidence From Human Neuroimaging Studiesmentioning
confidence: 99%
“…Similar preparatory signals have been observed using invasive electrophysiology (8, 9) and functional MRI (7, 10), and have been demonstrated also for choices between multiple-response options (6,7,10), for abstract decisions (10), for perceptual choices (11), and for value-based decisions (12). To date, the exact nature and causal role of such early signals in decision making is debated (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%